2016
DOI: 10.4067/s0718-16202016000300004
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Sediment Yield in the First Year After Replacement of Pastures by Sugarcane

Abstract: , we created land use/land cover maps. We then quantified the changes in composition and configuration by using landscape metrics and an adjacency matrix. By 2007, the dominant land cover had changed from agriculture to native vegetation. Residential areas showed the largest relative increase (670%) and had significant adjacency with native vegetation. The native vegetation increased by 375 ha, but the number of patches decreased by 45% and the mean patch area increased by 124%, which indicated that fragmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…A negative impact induced by conversion from pasture to sugarcane was found by Youlton et al [44] in a Quartzipsamments with 12% clay, who reported that runoff was increased in sugarcane just after the conversion due to soil disturbance and absence of soil cover. However, results from soil porosity and bulk density in SCplant showed a higher potential of water infiltration in comparison to PA, considering that about 3% of the amount of total rainfall might cause runoff near the city of Brotas-SP [41].…”
Section: Conversion From Pasture To Sugarcane Cultivationmentioning
confidence: 84%
See 1 more Smart Citation
“…A negative impact induced by conversion from pasture to sugarcane was found by Youlton et al [44] in a Quartzipsamments with 12% clay, who reported that runoff was increased in sugarcane just after the conversion due to soil disturbance and absence of soil cover. However, results from soil porosity and bulk density in SCplant showed a higher potential of water infiltration in comparison to PA, considering that about 3% of the amount of total rainfall might cause runoff near the city of Brotas-SP [41].…”
Section: Conversion From Pasture To Sugarcane Cultivationmentioning
confidence: 84%
“…However, results from soil porosity and bulk density in SCplant showed a higher potential of water infiltration in comparison to PA, considering that about 3% of the amount of total rainfall might cause runoff near the city of Brotas-SP [41]. Besides, during sugarcane ratoon cultivation, there is no additional soil disturbance, and plant canopy plus crop residues could substantially reduce the risks of soil erosion and soil losses [41,44].…”
Section: Conversion From Pasture To Sugarcane Cultivationmentioning
confidence: 97%
“…Comparando estas tasas de pérdida de suelo con otros estudios en Colombia, como el realizado en el cultivo de caña para panela en Cundinamarca, los valores obtenidos en este trabajo son menores a las registradas a través de la implementación de un simulador de lluvia, que en cultivos con corte por parejo y una inclinación topográfica de 35 %, la pérdida de suelo anual estimada mediante la aplicación del modelo USLE fue de 27 t ha -1 año -1 (Tauta Muñoz et al, 2018). La pérdida de suelo durante el primer año de desarrollo de un cultivo de Siembra 10(2) (2023) | e5435 ISSN-e: 2477-8850 | ISSN: 1390-8928 caña de azúcar en un suelo con 9 % de pendiente fue de 2,58 t ha -1 año -1 (Youlton et al, 2016), valores similares a los encontrados en el presente estudio. En la Figura 6 se puede observar la pérdida de suelo acumulada durante el tiempo del desarrollo vegetativo del cultivo, así como la precipitación mensual durante dicho periodo.…”
Section: Resultados Y Discusiónunclassified
“…The tests took place in an experimental 100 m 2 field plot (5 m wide by 20 m long) without vegetation cover and delimited with metal sheets approximately 30 cm high (see Figure 4). The plots were installed in 2011 [33][34][35] and surface runoff and erosion have been monitored continuously [36,37]. The experiment was carried out at Instituto Arruda Botelho (IAB), Itirapina, central region of the State of São Paulo, Brazil (latitude 22 • 10 S, longitude 47 • 52 W, elevation of 790 m).…”
Section: Field Tests and Study Area Descriptionmentioning
confidence: 99%